Information and Communication Technologies in Education, Research, and Industrial Applications 9th International Conference, ICTERI 2013, Kherson, Ukraine, June 19-22, 2013, Revised Selected Papers - Ermolayev, Vadim; Mayr, Heinrich C.; Nikitchenko, Mykola; Spivakovsky, Aleksander; Zholtkevych, Grygoriy (Communications in Computer and Information Science, 2013)
This book constitutes the thoroughly refereed proceedings of the 9th International Conference on Information and Communication Technologies in Education, Research, and Industrial Applications, held in Kherson, Ukraine, in June 2013. The 18 revised full papers presented were carefully reviewed and selected from 125 submissions. The papers are organized in topical sections on systems, infrastructures, and integration; semantics, knowledge engineering and management; ICT in teaching methodologies and didactics; model-driven software development and verification.